Individual, Family, and Community Transformations through Opportuni-ties Facilitated by Technical Vocational Education and Training (TVET) - Narsico, Peter G.; Narsico, Lalaine O.; Rio , Rachel B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study explores how individuals strive to improve their livelihoods by leveraging accessible opportunities. It aimed to evaluate the outcomes of Technical-Vocational Education and Training (TVET) programs on participants, along with the subsequent effects on their families and immediate community, emphasizing the programs' transformative influence. The research highlights the intersection of poverty alleviation, employment, education, and industry—core elements of the United Nations' Sustainable Development Goals. The investigation was conducted in a neighborhood in Cebu City, Philippines, conveniently located near a technical-vocational training center. A qualitative approach, specifically using case study methodology, was employed. Convenience sampling was used to gather information, leading to interviews with consenting participants. Additionally, observations from nearby residents who have witnessed the community’s changes over time served as supplementary data. The study sought to understand respondents' personal experiences with training programs, the effects on their families and immediate community, their unique circumstances, and the key insights and significant implications. The findings reveal that skills training improves employability, helps meet basic needs, and enhances the quality of life at individual, family, and community levels. The study concludes that skills training has a transformative impact on these three areas. However, to fully optimize its positive effects, skills training should be supplemented with additional initiatives.